Hubungan Antara Konsep Diri dan Gaya Hidup dengan Intensitas Penggunaan Gadget Pada Remaja Kelas X di MAN Kota Binjai - Nun Zairina (Universitas Islam Negeri Sumatera Utara Medan, 2021)
This study aims to determine the relationship between self-concept and lifestyle with the intensity of gadget use in adolescents. There are three hypotheses proposed in this study, namely the first, there is a relationship between self-concept and lifestyle with the intensity of gadget use in adolescents. Second, there is a relationship between self-concept and the intensity of gadget use in adolescents. Third, there is a relationship between lifestyle and the intensity of gadget use in adolescents. The data collection method uses a psychological scale which includes a 28item gadget use intensity scale, a self concept scale of 47 items, and a lifestyle scale of 31 items. The analysis technique is using multiple regression analysis techniques assisted by using SPSS 25.0 for windows. The subjects in this study were teenagers at MAN KOTA BINJAI, as many as 90 students, who were taken using proportional random sampling technique. The results showed Rx1.2y = 0.379 with F = 1.1441 and p = 0.002 (p < 0.01) which means that there is a relationship between self-concept and lifestyle with the intensity of gadget use in adolescents. The results obtained provide an effective contribution of 29.9 % and 70.1% were influenced by other factors outside of this study. The value of rx1y = 0.262 and p = 0.000 (p < 0.01) which means that there is a significant positive relationship between self-concept and the intensity of gadget use in adolescents. The value of rx2y = 0.315 and p = 0.002 (p < 0.01) which means that there is a significant positive relationship between lifestyle and the intensity of gadget use in adolescents.